Betawi Culture as Cultural Capital in Resilience Against Flood Disasters - Aminullah, Muhammad; Sari, Annisa Ananda (Cities and Urban Development Journal, 2024)
Background: As a region that is downstream of 13 rivers, Jakarta is called a water city that has a natural vulnerability to disasters. Thus, river management is a challenge for Jakarta. Aims: This study examines how the cultural capital of the Betawi Community is currently being revived by the Padepokan Ciliwung Condet in managing the Ciliwung River and how this cultural capital can have an impact on disaster resilience. Methods: This study uses a qualitative approach. This study conducted observations, in-depth interviews, and literature studies to identify the cultural capital used by the community. Results: The results of the study show that the cultural capital applied by the Ciliwung Condet Padepokan Community (KPCD) consists of physical infrastructure and intangible beliefs that connect humans and rivers as twins. KPCD's strategy in flood resilience includes river boundary conservation and education to strengthen the Betawi Cultural perspective on rivers. Conclusion: This study indicates that this approach can be an effective model in flood disaster mitigation in urban areas by utilizing local wisdom and traditional culture. In line with Bourdieu's social capital theory which emphasizes the importance of cultural capital in building community resilience to environmental threats.